Selective transitional zone sampling approach versus random biopsy in cases with malignant liver masses: Is there any superiority? - Kosti Can ÇALIŞKAN,; Banu ÖZGÜVEN,; Mehmet Sait BUĞDACI,; Emin ÇAKMAKCI,; Umut Perçem ORHAN,; Mehmet ERTÜRK,; Zeki KARPAT,; Muzaffer BAŞAK,; Fatih SELÇUKBİRİCİK, (Turkish Journal of Gastroenterology, 2019)
-